2008
DOI: 10.1111/j.1538-7836.2008.03080.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative anticoagulation in patients having implantation of a cardiac pacemaker or defibrillator: a systematic review and practical management guide

Abstract: To cite this article: Jamula E, Douketis JD, Schulman S. Perioperative anticoagulation in patients having implantation of a cardiac pacemaker or defibrillator: a systematic review and practical management guide. J Thromb Haemost 2008; 6: 1615-21.Summary. Background: The perioperative management of anticoagulation in patients who are having implantation of a pacemaker or implantable cardioverter defibrillator (ICD) is a common clinical problem in which best clinical practise is not established. Methods: We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 16 publications
(35 reference statements)
4
51
0
1
Order By: Relevance
“…17 However, other data indicate that an elevated risk for pocket hematoma exists in patients who undergo pacemaker implantation without interruption of oral anticoagulation. 18 It also has been demonstrated that use of heparin initiated 6 or 24 hours after implantation or use of high doses of heparin may significantly increase the risk of bleeding. 10,18 In a meta-analysis study, 18 the perioperative management of patients with a high risk of TE event was not established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, other data indicate that an elevated risk for pocket hematoma exists in patients who undergo pacemaker implantation without interruption of oral anticoagulation. 18 It also has been demonstrated that use of heparin initiated 6 or 24 hours after implantation or use of high doses of heparin may significantly increase the risk of bleeding. 10,18 In a meta-analysis study, 18 the perioperative management of patients with a high risk of TE event was not established.…”
Section: Discussionmentioning
confidence: 99%
“…18 It also has been demonstrated that use of heparin initiated 6 or 24 hours after implantation or use of high doses of heparin may significantly increase the risk of bleeding. 10,18 In a meta-analysis study, 18 the perioperative management of patients with a high risk of TE event was not established. Managing patients with a high risk for TE events continues to be difficult and requires further study to establish a recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, antiplatelet therapy can be safely discontinued for a period of 5-7 days, especially when recommended for primary prevention [16,17]. Additionally, the use of heparin (UFH or LMWH) as bridging therapy during interruption of OAC increased the risk of bleeding and some authors suggest performing implantation procedures without OAC therapy cessation [18,19]. There are no data available regarding periprocedural treatment of patients treated previously with new OAC.…”
Section: Discussionmentioning
confidence: 99%
“…10-13 BT offered no advantages in any of these studies and might even have increased bleeding events. 12 Furthermore, heparin bridging prolongs hospitalization, 14,15 and may also contribute to the observations that patients with acute coronary syndromes while on long-term OAC are significantly less likely to undergo coronary angiography and PCI, and waiting times for these procedures are longer in the OAC-treated patients than in those not on OAC. 14 In AF patients on OAC, effective anticoagulation is necessary during PCI not only to avoid thromboembolic complications, but also to avoid thrombotic complications of the intervention.…”
Section: Discussionmentioning
confidence: 99%